Agrarian reform as unfinished business : (Oxford University Press, 1977)
This collection comprises a generous selection of Ladejinsky's best and most significant writings ans spans his entire professional career, representing every Asia country. This collection brings cogency and illumination to the human and institutional realities tha chalenge us with the unfinished business of agrian reform.